MicroRNAs Regulate Metabolic Phenotypes During Multicellular Tumor Spheroids Progression - Muciño-Olmos, Erick Andrés; Vázquez-Jiménez, Aarón; López-Esparza, Diana Elena; Maldonado, Vilma; Valverde, Mahara; Resendis-Antonio, Osbaldo (Frontiers in Oncology, 2020)
During tumor progression, cancer cells rewire their metabolism to face their bioenergetic demands. In recent years, microRNAs (miRNAs) have emerged as regulatory elements that inhibit the translation and stability of crucial mRNAs, and components that directly trigger some of the metabolic alterations in cancer. In this study, we investigated the relationship between miRNAs and their targets mRNAs codifying metabolic genes, and how this fine-tuned regulation is diversified depending on the tumor stage. To do so, we implemented a paired analysis of RNA-seq and small RNA-seq in a breast cancer cell line (MCF7), it cultured in multicellular tumor spheroid (MCTS) and monoculture conditions. For MCTS, we selected two-time points during their development, primarily to recapitulate a proliferative and quiescent stage and contrast their metabolic phenotypes. As a result, we identified a set of new direct putative regulatory interactions between miRNAs and metabolic mRNAs representative for proliferative and quiescent stages. Notably, our study allows us to suggest that miR-3143 regulates the carbon metabolism by targeting hexokinase-2. We also determined that the overexpression of several miRNAs directly overturn the expression of mRNAs that control glycerophospholipid and N-Glycan metabolism. While this set of miRNAs downregulates their expression in the quiescent stage, the same set is upregulated in proliferative stages. This last finding suggested a metabolic switch of the above mentioned metabolic pathways between the quiescent and proliferative stages. Our results contribute to a better understanding of how miRNAs modulate the metabolic landscape in breast cancer MCTS, which eventually helps in designing strategies to reduce the cancer phenotype.